Characteristics of Biomass Brickets with Different Geometry Variations and Types of Raw Material - Ritzada, I Putu Dharma Putra; Yulianti, Ni Luh; Gunadnya, Ida Bagus Putu (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
This study aims to analyze the characteristics of biomass briquettes with different geometry variations and types of biomass briquette raw materials and determine which treatment produces the best quality briquettes. This research uses block design (RAK) using 2 factorials and 3 replications. The first factor is the type of raw material (A) which consists of three levels, namely tabah bamboo (A1), rice husk (A2) and a mixture of tabah bamboo and rice husk (A3). The second factor is the geometric shape of the briquette (B) which consists of two levels, namely beams (B1) and cylinders (B2). All treatments were repeated 3 times in order to obtain 18 observational data. The data obtained were analyzed by means of variance and if there was a significant treatment effect, then it was followed by the BNT test on the average treatment. The results showed that the interaction between treatments. Types of raw materials and geometric shapes had a significant effect on the quality parameters of the resulting briquettes. The treatment of briquettes made from rice husks in a cylindrical shape (A2B2) is a treatment that produces the best quality briquettes with a moisture content value of 2.64% bb.ash content was 6.60%, combustion rate was 73.16 (gr / minute) and volatile matter was 13.86%.